On the dynamic nature of Mo sites for methane dehydroaromatization. Issue 21 (10th May 2018) - Vollmer, Ina; van der Linden, Bart; Ould-Chikh, Samy; Aguilar-Tapia, Antonio; Yarulina, Irina; Abou-Hamad, Edy; Sneider, Yuri G.; Olivos Suarez, Alma I.; Hazemann, Jean-Louis; Kapteijn, Freek; Gascon, Jorge
Abstract : The dynamic catalytic site on Mo/HZSM-5 for methane dehydroaromatization is formed during the initial phases of the reaction. Labelling experiments show that carbon from the carbidic active site is incorporated into the final products. Abstract : The mechanism of methane activation on Mo/HZSM-5 is not yet fully understood, despite the great interest in methane dehydroaromatization (MDA) to replace aromatics production in oil refineries. It is difficult to assess the exact nature of the active site due to fast coking. By pre-carburizing Mo/HZSM-5 with carbon monoxide (CO), the MDA active site formation was isolated from coke formation. With this a clear 13 C NMR signal solely from the active site and not obscured by coke was obtained, and it revealed two types of likely molecular Mo (oxy-)carbidic species in addition to the β-Mo2 C nanoparticles often mentioned in the literature. Furthermore, separating the active site formation from coking by pre-carburization helped us examine how methane is activated on the catalytic site by carrying out MDA using isotopically labelled methane ( 13 CH4 ). Carbon originating from the pre-formed carbide was incorporated into the main products of the reaction, ethylene and benzene, demonstrating the dynamic behavior of the (oxy-)carbidic active sites.